Hydraulic flow rate increase maneuver for ichthyofauna repulsion in bulb-type generating units – Jirau Hydroelectric Power Plant - Silva, Tania Machado da; Figueiredo, Wllyane Silva; Zara, Luiz Fabrício (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
Several repulsion systems have been developed to minimize the confinement of ichthyofauna in draft tubes. In this perspective, this study intends to analyze the efficiency of the hydraulic flow rate increase maneuver, using a hydroacoustic system for real-time monitoring of the movement of the ichthyofauna confined within the draft tube of the generating units of Jirau Hydroelectric Power Plant. It is located on the Madeira River, in Rondônia, Brazil. We analyzed footage of 105 machine shutdowns taken between 2019 and 2020 at Jirau Hydroelectric Power Plant that used the hydraulic flow rate increase maneuver as a strategy to repulse ichthyofauna. Also, the footage of 7 two-stage shutdowns in the year 2020 was analyzed, the first stage without the maneuver and the second with the maneuver. The follow-up of 105 shutdowns demonstrate that approximately 85% of the footage showed little or no movement of ichthyofauna in the draft tube, with images of movements showing patterns characteristic of small fish ( 97%). Furthermore, the quantitative evaluation of the two-stage maneuver indicated a reduction of approximately 91% in the movement of ichthyofauna after the hydraulic flow rate increase maneuver. Thus, the increase in the rate of the hydraulic flow procedure, developed by Jirau Energia, proved to be an innovative and efficient strategy in reducing extensive social and environmental impacts and in favoring positive economic impacts.